Avian Influenza Virus A (H5N1), Detected through Routine Surveillance, in Child, Bangladesh - Brooks, W. Abdullah (Centers for Disease Control and Prevention, 2009)
We identified avian influenza virus A (H5N1) infection in a child in Bangladesh in 2008 by routine influenza surveillance. The virus was of the same clade and phylogenetic subgroup as that circulating among poultry during the period. This case illustrates the value of routine surveillance for detection of novel influenza virus.